Analisis Rendahnya Availability Mesin Strip Siebler 1 menggunakan Metode Overall Equipment Effectiveness (OEE) di PT Kimia Farma - Rahmat Arif Suntara; Tiaradia Ihsan (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to analyze the causes of the low availability value of the Siebler 1 machine at PT Kimia Farma using the Overall Equipment Effectiveness (OEE) approach. The research method employed is descriptive quantitative, utilizing machine operational data from January to October 2025. The three main components of OEE—availability, performance, and quality were calculated and analyzed to identify the factors that most significantly affect machine effectiveness. The results indicate that the average OEE value of the Siebler 1 machine is 37.68%, which is far below the industrial effectiveness standard of 85%. Availability is identified as the main contributor to the low OEE, with an average value of only 53.40%, caused by high downtime resulting from mechanical failures in the feeder and heating unit, as well as inconsistent implementation of preventive maintenance. Meanwhile, the performance and quality components have average values of 69.08% and 99.3%, respectively, indicating that product quality is not the primary issue. Based on the fishbone diagram analysis, the main causes of low effectiveness stem from machine-related factors and work methods, leading to increased unplanned downtime.